Becoming Undone: The Shifting Identities of the Pilegesh as Narrative Logic and Rhetorical Key in Judges 19 - Nessler, Brent (The catholic biblical quarterly, 2025)
Biblical scholars have long approached Judges 19 with guarded trepidation, not only because of its brutality but also because of its narrative and rhetorical difficulties. Many scholars have sought coherence in the characterizations of the Levite and the פלגש or פילגש (pīlegeš; pîlegeš; pilegesh), including cursory references to the unique designations the text provides its anonymous protagonists. But these passing observations either (1) focus on the Levite, despite his comparative "stability," or (2) comment on some, but not all, of the pilegesh’s varied identities. For these reasons, the characterization and narrative function of the pilegesh demand further inquiry, and the lingering opacity of Judges 19 necessitates fresh insights. Therefore, through literary analysis and an application of insights from trauma studies, I contend that the pilegesh of Judges 19 resists static interpretations of her character, instead embodying a figure whose dynamic characterization as a woman in traumatic decline provides the interpretive key to the narrative logic and rhetorical force of the entire pericope. To support this claim, I first define פילגש as the "stabilizing" identity to which the woman always returns. Next, I trace the plot of Judges 19 by way of analyzing the pilegesh’s "shifting" identities ("girl," vv. 3-9; "slave," v. 19; detached "woman," vv. 26-27; "pieces," v. 29). Finally, I consider the rhetorical impact of the pilegesh’s dynamic anonymity, namely, how it compels the reader to witness the narrative as she does, silent and helpless, while also granting a "voice" to her experience in the text, provoking empathy through terror.